The Concept Of "Public Council": Essence and Content - Akhmedov Tuychi Adashevich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article thoroughly explores the essence and content of the concept of the "public council." In particular, the importance of the public council as a concept, its differences from other councils, its narrow and broad meanings, approaches to the public council, its theoretical and methodological foundations, and scholars' views have been studied. The author's position on the public council is expressed.